Describing brown as green: an examination of the relationship between greenwashing and consumer negative emotive outcomes - Sayibu Ibrahim Nnindini; Justice Boateng Dankwah (Cogent Business & Management, 2024)
As the demand for sustainable and environmentally friendly products continues to rise, consumers have become more discerning in their brand choices. This has resulted in many companies resorting to greenwashing to appear environmentally friendly. While previous studies have explored different dimensions of greenwashing, its effects on consumer emotive outcomes have not been given much scholarly attention. Therefore, this study sought to examine the relationship between greenwashing and consumer negative emotive outcomes. Additionally, the study examined the potential moderating effect of brand loyalty on the relationship between greenwashing and these negative emotive outcomes. A cross-sectional survey involving a total of 490 respondents with usage experience of green household electronic appliances was utilized. Data were analyzed using the partial least squares-structural equation modeling (PLS-SEM) approach. The results of the analysis revealed a positive correlation between greenwashing and all four negative emotive outcomes examined. Furthermore, the findings demonstrated that brand loyalty plays a positive moderating role in the relationship between greenwashing and negative emotive outcomes. The study thus, strongly recommends that brands engaged in greenwashing discontinue the practice. The consequences of the negative outcomes associated with greenwashing extend beyond a decline in sales performance. It could potentially inflict significant damage on the corporate brand image and reputation. Therefore, brands should prioritize genuine environmental responsibility to mitigate these adverse effects and maintain a positive brand image among consumers.
Keywords: 650; Greenwashing; brandavoidance; brand hate; brand retaliation; brandboycott; brand loyalt